A breath Full of Life – The Importance of Movement and Physiotherapy in the Treatment of Children with Cystic Fibrosis - Oświeczyńska, Katarzyna; Sowa, Aleksandra; Trząsalski, Kacper; Jędrzejewska-Rzezak, Patrycja (Quality in Sport, 2025)
Cystic fibrosis is a congenital genetic disease that cannot be acquired or passed on through contact with another person. It occurs in both boys and girls because its cause is a genetic mutation present from birth. The disease develops when a child inherits two defective genes - one from the mother and the other from the father. Parents, although not suffering from the disease themselves, are carriers of the mutation and can pass it on to their offspring. Chronic inflammation gradually destroys the lung parenchyma, causing changes such as bronchodilation, fibrosis and sometimes emphysema or atelectasis. As the disease progresses, respiratory failure occurs, leading to hypoxia and a significant reduction in physical endurance in patients with cystic fibrosis. Regular physical activity and properly selected physiotherapy are a key component of cystic fibrosis therapy. They support the functioning of the respiratory system, improving patients' quality of life. Systematic exercise and specialized drainage techniques facilitate the removal of secretions from the lungs, strengthen respiratory muscles and increase overall fitness.